Molecular characterization and genotype of multi-drug resistant Staphylococcus epidermidis in nasal carriage of young population, Mahasarakham, Thailand - Peechanika Chopjitt; Panita Tangthong; Jiranuch Kongkaem; Pritprapoan Wonkyai; Achira Charoenwattanamaneechai; Surasak Khankhum; Phitcharat Sunthamala; Anusak Kerdsin; Nuchsupha Sunthamala (Biomolecules & Biomedicine)
Staphylococcus epidermidis, a coagulase-negative staphylococcus, is a prevalent skin commensal that has increasingly been recognized as a significant pathogen, particularly in hospital environments, where it is associated with device-related infections. The emergence of multi-drug resistance and its ability to form biofilms complicate the clinical management of infections caused by this organism, posing a growing public health concern. This study aimed to investigate the nasal carriage of S. epidermidis among healthy young individuals and to analyze its antibiotic resistance patterns, resistance genes, and biofilm formation capabilities. Nasal swabs were collected from 40 undergraduate students at Mahasarakham University, Thailand, aged between 20 and 22 years. A total of 38 isolates were confirmed as S. epidermidis through both phenotypic and molecular characterization. Antibiotic susceptibility testing demonstrated resistance to various classes of antimicrobials, including beta-lactams, macrolides, and tetracyclines. Notably, five isolates exhibited methicillin resistance S. epidermidis (MRSE). Resistance genes, such as mecA, ermA, tetM, tetL, and tetK, were identified across the isolates, contributing to the observed resistance profiles. Biofilm formation assays revealed that most isolates displayed weak to moderate biofilm formation, with only one isolate demonstrating strong biofilm-forming capacity. Genetic analysis indicated a significant correlation between biofilm formation and the presence of the icaA gene, which is crucial for biofilm production. This study suggests the necessity for ongoing surveillance of nasal carriage of S. epidermidis to enhance understanding of its role in the dissemination of antimicrobial resistance and biofilm-associated infections, particularly within healthcare settings.